Socio-economic factors associated with online health information seeking in the European Union: a panel data analysis (2016–2024) - Hasan Fehmi Demirci (BMC Public Health, 2026)
Abstract Objective This study aims to investigate socio-economic factors associated with online health information seeking in the digital health environment across 27 European Union countries between 2016 and 2024. Method The analysis used a balanced panel dataset comprising 27 European Union countries for the period 2016 through 2024. The independent variables used include tertiary education attainment, income inequality (Gini coefficient), GDP per capita, internet access, age dependency ratio, and government and compulsory health care financing schemes. GDP per capita and government and compulsory health care financing schemes were log-transformed to reduce skewness and to allow the coefficients to be interpreted with respect to proportional changes. The panel regression model was selected based on the two-way fixed effects model after reviewing the F-test, Hausman test, and Lagrange multiplier test results. Findings The results from the best-fitting fixed effect model indicated that tertiary education (β = -1.180, p = 0.004), log GDP per capita (β = 25.265, p < 0.001), internet access (β = 0.665, p < 0.001), and age dependency ratio (β = -0.652, p < 0.001) were significantly associated with online health information seeking behavior. Income inequality (β = -0.371, p = 0.356) and log health financing (β = -1.642, p = 0.380) were not statistically significantly associated. Conclusion The study has shown that there is a significant association among economic development, internet access, and demographic dependency ratios regarding the search for health information on the Internet in EU member states. Internet access showed a positive and statistically significant association with online health information seeking.